Assessment and model guided cancer screening promotion by village doctors in China: a randomized controlled trial protocol. Issue 1 (December 2015) - Feng, Rui; Shen, Xingrong; Chai, Jing; Chen, Penglai; Cheng, Jing; Liang, Han; Zhao, Ting; Sha, Rui; Li, Kaichun; Wang, Debin
Abstract Background Proven cost-effectiveness contrasted by low uptake of cancer screening (CS) calls for new methodologies promoting the service. Contemporary interventions in this regard relies primarily on strategies targeting general or specific groups with limited attention being paid to individualized approaches. This trial tests a novel package promoting CS utilization via continuous and tailored counseling delivered by primary caregivers. It aims at demonstrating that high risk individuals in the intervention arm will, compared to those in the delayed intervention condition, show increased use of CS service. Methods/Design The trial adopts a quasi-randomized controlled trial design and involves 2160 high risk individuals selected, via rapid and detailed risk assessments, from about 72, 000 farmers aged 35+ in 36 administrative villages randomized into equal intervention and delayed intervention arms. The CS intervention package uses: a) village doctors and village clinics to deliver personalized and thus relatively sophisticated CS counseling; b) two-stage risk assessment models in identifying high risk individuals to focus the intervention on the most needed; c) standardized operation procedures to guide conduct of counseling; d) real-time effectiveness and quality monitoring to leverage continuous improvement; e) web-based electronic system to enable prioritizing complex determinants of CS uptake and tailoring counseling sessions to the changing needs of individual farmers. The intervention arm receives baseline and semiannual follow up evaluations plus CS counseling for 5 years; while the delayed intervention arm, only the same baseline and follow-up evaluations for the first 5 years and CS counseling starting from the 6th year if the intervention proved effective. Evaluation measures include: CS uptake by high risk farmers and changes in their knowledge, perceptions and self-efficacy about CS. Discussion Given the complexity and heterogeneity in the determinant system of individual CS service seeking behavior, personalized interventions may prove to be an effective strategy. The current trial distinguishes itself from previous ones in that it not only adopts a personalized strategy but also introduces a package of pragmatic solutions based on proven theories for tackling potential barriers and incorporating key success factors in a synergetic way toward low cost, effective and sustainable CS promotion. Trial registration ISRCTN33269053